Using Assisting Aids For Developing Motor Speed And Its Effect On Maximal Anaerobic Ability And The Motor Speed Of Basketball Defense Players U18 - Abedulsattar, Muhanned; Majeed, Omar (Journal of Physical Education, 2016)
The importance of the research lies in using assisting aids that develop the motor speed of players and their effect on maximal anaerobic ability and the players' motor speed in basketball defense. The problem of the research is that physical preparation did not take its role in the training process. The researchers used the experimental method. The subjects were (8) under eighteen basketball players from the National Center for gifted in Basketball for the season 2015 – 2016. The data was collected and treated using SPSS to come up with the conclusions. The researchers concluded that these assisting aids develop the motor speed and maximal anaerobic speed of defense basketball player. They also concluded that the assisting aids develop physical performance as well as functional performance. The researcher recommended the necessity of dedicating few training days for developing defense skills as well as paying attention to physical abilities all season long